2014
DOI: 10.1007/s12650-014-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Visualization study of hybrid synthetic jets

Abstract: A synthetic jet (SJ) is a fluid flow that is created from an oscillatory process of suction and blowing. A hybrid synthetic jet (HSJ) combines this principle with fluidic pumping through a valveless pump. The present study addresses round HSJs issuing into quiescent surroundings from an actuator orifice 8 mm in diameter. For comparison purposes, a common (zero-net-mass-flux) SJ is used. The working fluid is air, and the maximum Reynolds numbers are 11,000 and 9,000 for HSJs and SJs, respectively. The following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 63 publications
3
22
0
Order By: Relevance
“…The advantages of the HSJA are evident: For P e = 0.4-3.2 W, the HSJA achieves a 15-23% increase in the velocities and a 41-48% increase in the energetic efficiency. These results well agree with the previous experiments with the same actuator, which were performed at a bit higher input real power, P e = 4.0 W, see [43,48,55]. Namely, the studies [43, 48, and 55] concluded that the HSJA achieves a 25%, 24%, and 26 % increase of the velocities in comparison with the SJA, respectively.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The advantages of the HSJA are evident: For P e = 0.4-3.2 W, the HSJA achieves a 15-23% increase in the velocities and a 41-48% increase in the energetic efficiency. These results well agree with the previous experiments with the same actuator, which were performed at a bit higher input real power, P e = 4.0 W, see [43,48,55]. Namely, the studies [43, 48, and 55] concluded that the HSJA achieves a 25%, 24%, and 26 % increase of the velocities in comparison with the SJA, respectively.…”
Section: Resultssupporting
confidence: 90%
“…An important parameter that is going to be observed in this study is the efficiency of the SJA. A generalized version of the energetic efficiency definition from [48] will be used. The generalization dwells in the extension of the definition for non-uniform velocity profiles and in relating the mean fluid kinetic energy rate to the input real power,…”
Section: Parametersmentioning
confidence: 99%
See 3 more Smart Citations